American English in Belles-Lettres - Martyniuk, J.; Mikhalchuk, O. M.; Мартинюк, Ю.; Михальчук, О. М. (Вінницька міська друкарня, 2020)
The article explores the study of the distinctive features of American literature and analyzes the literary representation of American English.
Американська англійська мова в художній літературі
Keywords: English; fiction; American English